EVALUATION OF SPORTS AND HEALTH PHYSICAL EDUCATION PROGRAM IN SMA N 2 NGAWI USING THE CIPP EVALUATION MODEL (CONTEXT, INPUT, PROCESS, PRODUCT). - Fantas Setyadi; M. Furqon Hidayatullah; Sapta Kunta Purnama (Indonesia Sport Journal, 2021)
The purpose of the study is to evaluate the physical health and sport education at SMA N 2 Ngawi using a context, input, process, product (CIPP) evaluation model approach. The research method used in this research is program evaluation. The approach taken in this program evaluation research uses the CIPP evaluation model (Context, Input, Process, Product). Sources of research data are principals, teachers, and students. The data collection technique used is an assessment questionnaire instrument / score scale questionnaire. The data obtained were then analyzed using quantitative descriptive data analysis techniques. This study found that the results of the context evaluation were 83.69% in the good category, the results of the input evaluation were 84.40% in the good category, the process evaluation results were 86,67% in the good category, and the product evaluation results were 89.60 in the good category. Based on the results of the CIPP evaluation research, it can be concluded that the physical health and sport education program at SMA N 2 Ngawi is in the good category with an achievement value of 86.09%.Keywords: Physical Education, Sports, Health, CIPP Evaluation, School.